Law Implementation for Drug Abuse: Between Prison and Rehabilitation - Eka Ari Endrawati (Budapest International Research and Critics University, 2022)
Drug sales is strictly prohibited if it is misused by certain parties. This is because the threats that arise can threaten the existence of the younger generation who will lead the nation in the future. The sanctions for someone who abuses or distributes drugs without permission and without rights are determined as a result of punishment. This is qualitative research with a phenomenological approach. Data collection was done by semi structured interview with 20 people, namely students who have experienced in drug abused, BNN (National Board of Narcotics and Addictive Substances) Officer, University leaders, Head of prison and Legal practitioners to get the perspectives on how rehabilitation and law enforcement should be implemented without bias meaning. The result of this research shows that the Law on Narcotics is the authority of judges to pass a sentence on a narcotics abuser to carry out rehabilitation. This authority recognizes that narcotics abusers, apart from being perpetrators of criminal acts, are also victims of the crime itself. Criminal sanctions are expected to have a deterrent effect on perpetrators of crimes. However, apart from punishment, drug users are also given rehabilitation, namely medical rehabilitation and social rehabilitation, as stated in the Supreme Court Circular Letter No. 4 of 2010.